Estimation of Wheels’ Normal Reaction Forces of Automobile in Steady-State Curvilinear Motion - Piotr Fundowicz; Hubert Sar; Mateusz Brukalski (Communications - Scientific letters of the University of Zilina, 2021)
Computer simulation seems to be one of the cheapest and relatively fast methods of investigating vehicle motion. Thereby, it may be important in the case of calculations for the reconstruction of traffic incidents. In particular, that may be important to answer the following question: How wheels’ normal reaction forces differ during the cornering of a vehicle? In this article, the authors presented how the normal reaction forces vary in the case of roll motion of a vehicle body. Suitable mathematical equations are presented. Furthermore, the measurements of the height of the centre of gravity were performed, which was necessary to obtain the normal reaction forces while vehicle body rolls. The authors decided to apply dimensionless coefficients, which represented the properties of a front and rear suspension. Additionally, dimensionless parameters were applied to consider the impact of asymmetrical distribution of vehicle load on normal reaction forces of wheels on a road surface.